Changes in morphology of white blood cells on peripheral smear in COVID-19 infection - Agarwal, Garima; Gupta, Shubhangi; Singh, Natasha; Mittal, Salony; Verma, Atul; Bindra, Manjit S.; Garg, Gaurav (International Journal of Research in Medical Sciences, 2021)
Background: COVID-19 is an infectious disease caused by a newly discovered coronavirus, and has spread around the world in a deadly pandemic. The first case of COVID-19 was reported from Wuhan, China in December 2019. This is also called as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) because of its homology with SARS virus. The most common hematological manifestation of coronavirus is lymphopenia which is due to depletion of lymphocytes by coronavirus infection. Other manifestations are neutrophilia and mild thrombocytopenia. Literature is full of quantitative hematological parameters but the researches on morphology of white blood cells is still ongoing. We at our institute done study on 60 confirmed positive cases of COVID-19, and analyzed those peripheral smears in terms of morphology of white blood cells. Methods: The study was done using peripheral smear staining with methylene blue stain and was screened for various changes in white blood cells in peripheral smear. Results: Changes in the white blood cells were examined in the peripheral smear and findings were made in the tabular form. Conclusions: To conclude that all these changes are due to the virus infecting them or are secondary to pathogenesis of COVID disease, needs to be evaluated by larger studies.